Application of a nature-based solution adaptive management framework for improving coastal resiliency in a highly urbanized environment - McQueen, Andrew; Suedel, Burton; Copp Franz, Sara; Cardona, Tina; McDermott, Molly; Collins, Sabrina; Magar, Victor; Herzog, Jeffrey (Frontiers in Ecology and Evolution, 2025)
With the simultaneous rise in coastal flooding risks projected by current climate models and the escalating demands placed on urban infrastructure by population expansion, there is an urgent need for resilient solutions to address these challenges. In response, the adoption of nature-based solutions (NbS) and natural and nature-based features (NNBF) has gained traction as promising, cost-efficient approaches to bolster coastal resilience while offering additional economic, social, and environmental benefits as compared with traditional “gray” infrastructure. While progress has been made in developing and documenting NbS and NNBF approaches for flood risk management globally, uncertainties persist regarding their practical application and effectiveness in highly urbanized coastal environments. Therefore, the objective of this study was to examine the current understanding of NNBF for coastal resilience, providing insights into their potential applications and opportunities in urban coastal settings. To meet this objective, an NNBF principled approach was applied using the City of Boston coastal storm risk management study as an illustrative example. The initial phases of the NNBF guidelines framework was an effective means of organizing and communicating information relevant to the identification and down selection of NNBF alternatives for the region. This study provides valuable insights into the challenges and opportunities of incorporating innovative NbS and NNBF approaches for flooding risks in coastal urban regions.